Grasshopper herbivory immediately affects element cycling but not export rates in an N‐limited grassland system. Issue 3 (26th March 2021) - Potthast, Karin; Meyer, Stefanie; Tischer, Alexander; Gleixner, Gerd; Sieburg, Anne; Frosch, Torsten; Michalzik, Beate
Abstract: As a cause of ecosystem disturbances, phytophagous insects are known to directly influence the element and organic matter (OM) cycling in ecosystems by their defoliation and excretion activity. This study focuses on the interplay between short‐term, insect herbivory, plant responses to feeding activity, rhizosphere processes, and belowground nutrient availability under nutrient‐poor soil conditions. To test the effects of insect herbivory on OM and nutrient cycling in an N‐limited pasture system, mesocosm laboratory experiments were conducted using Dactylis glomerata as common grass species and Chorthippus dorsatus, a widespread grasshopper species, to induce strong defoliating herbivory. 13 CO2 pulse labeling was used together with labeled 15 N feces to trace the fate of C in soil respiration at the beginning of herbivory, and of C and N in above‐ and belowground plant biomass, grasshopper, feces, bulk soil, soil microbial biomass, throughfall solutions, and soil solutions. Within five days, herbivory caused a reduction in aboveground grass biomass by about 34%. A linear mixed‐effects model revealed that herbivory significantly increased total dissolved C and N amounts in throughfall solutions by a factor of 4–10 ( P  < 0.05) compared with the control. In total, 27.6% of the initially applied feces 15 N were translocated from the aboveground to the belowground system. A significant enrichment of 15 N in roots led to the assumption that feces‐derived 15 N was rapidly taken up to compensate for the frass‐related foliar N losses in light of N shortage. Soil microorganisms incorporated newly available 13 C; however, the total amount of soil microbial biomass remained unaffected, while the exploitative grass species rapidly sequestered resources to facilitate its regrowth after herbivory attack. Heavy herbivory by insects infesting D. glomerata ‐dominated, N‐deficient grasslands remarkably impacted belowground nutrient cycling by an instant amplification of available nutrients, which led to an intensified nutrient competition between plants and soil microorganisms. Consequently, these competitive plant–soil microbe interactions accelerated N cycling and effectively retained herbivory‐mediated C and N surplus release resulting in diminished N losses from the system. The study highlighted the overarching role of plant adaptations to in situ soil fertility in short‐term ecosystem disturbances.